PENGARUH TERPAAN BERITA MEDIA TENTANG PERUSAHAAN DAN PERSEPSI TANGGUNG JAWAB SOSIAL PERUSAHAAN TERHADAP PERSEPSI REPUTASI PERUSAHAAN GRUP DJARUM - Alyssa Jasmine Aurelia Rahmiqatrunnada; S. Rouli Manalu; Tandiyo Pradekso (Interaksi Online, 2023)
PT Djarum is one of the largest cigarette companies in Indonesia (Djarum, 2022). The media has reported that cigarette products are harmful. However, the media has also reported that the Djarum Group has a positive impact through their corporate social responsibility and business diversification efforts. This research was conducted with the aim of determining the influence of media news exposure about the company and perceptions of the company's social responsibility on the reputation perception of the Djarum Group using survey research methods. The theory used in this research is Attribution Theory. The sampling technique used was non-probability sampling. A total of 200 respondents from the Faculty of Social and Political Sciences, Diponegoro University, were selected as the research sample. Based on hypothesis testing, perceptions of the company's social responsibility influence the reputation perception of the Djarum Group. Media news exposure about the company does not affect the reputation perception of the Djarum Group. The perception of social responsibility has a 19.4 percent influence on the perception of the Djarum Group's reputation. Perceivers compare various information about the company's social responsibility and evaluate the consequences or outcomes of the observed company's behavior (Jones & Davis, 1965; Kelley & Michela, 1980). Furthermore, perceivers consider consensus, which refers to the extent to which other companies take certain actions in a situation, observations of the Djarum Group's repetitive behavior in certain or other situations, distinctiveness, and consistency, or the repetition of the Djarum Group's behavior over time in specific situations. Therefore, this information can ultimately influence an individual's perception of the company's reputation.